Interdisciplinary cooperation with solution-focused brief therapy to reduce job stress, burnout, and coping in Chinese nurses: A randomised controlled trial - Yan Kong; YanQi Zhang; Ping Sun; JinShu Zhang; Yang Lu; Juan Li; YingHua Zheng (Heliyon)
Background: Increased job stress and burnout are common among clinical nurses in China, reducing their work efficiency and nursing quality. Multiple studies have been conducted on brief interventions to reduce job stress and burnout among nurses. However, research has been hampered by a lack of psychological knowledge among nursing staff. Aim: To assess a solution-focused brief therapy for enhancing nurses' coping styles and mitigating job stress and burnout based on interdisciplinary cooperation. Design: This randomised controlled trial. Settings: We randomly allocated 60 nurses working at a tertiary general hospital in a city in China to an experimental (n = 30) or a control group (n = 30). Methods: A collaborative research team comprising psychology and nursing specialists was established to conduct this study. The control group received routine psychological intervention, whereas the intervention group received a solution-focused brief therapy based on interdisciplinary cooperation. Chinese nurses’ job stressors, Maslach Burnout Inventory, and simplified coping style questionnaire were used to evaluate both groups before and after the intervention. Results: A comparison of the scores for job burnout, total job stress, and positive coping before and after the interventions revealed significant improvements in the experimental group, whereas the scores for emotional exhaustion, depersonalisation, and total job stress in the control group demonstrated statistically significant differences. No significant differences were observed in the scores for negative coping, personal accomplishment, and coping style between the test and control groups before and after the intervention. Conclusions: Solution-focused brief therapy implemented through interdisciplinary collaboration effectively enhances clinical nurses' active coping style, alleviates job stress and burnout, and offers valuable guidance for nursing management practices.